Upacara Adat Tengger di Ambang Komodifikasi: Merawat Tradisi dari Ancaman Desakralisasi - Rahmi Febriani; Edi Dwi Riyanto (Universitas Andalas, 2021)
The phenomenon of profanation of sacred traditions in the tourism industry is increasingly prevalent. Considering that matter, some steps should be taken to avoid the tradition of desacralization. This research was done by a field research approach to identifying the values of the traditional ceremony of Tengger, especially Yadnya Kasada, Yadnya Karo, and Unan-unan. This research was located in Tosari and Ngadiwana Village, Tosari, Pasuruan, East Java. The data was collected by unstructured and open-ended interviews. The results showed that their beliefs and obedience in conducting the ancestral teachings must be balanced through a deep and comprehensive understanding of traditional values. On the other hand, adaptation strategies must be carried out to stabilize themselves with modernization. These are done to preserve the existence of tradition without eliminating the essence of sacredness that has been attached to it. Therefore, one of the steps that can be taken is to separate the tradition from commodification without resisting the flow of modernization